Cryptococcus bacillisporus causing cryptococcoma of the beak of an African grey parrot (Psittacus erithacus), Portugal - Carolina Silva; Carles Juan-Sallés; Joana Mendes; Ana Mendes; Mariana Ruivo; Juan L. Abad; Ferry Hagen; Maria F. Colom (Medical Mycology Case Reports, 2021)
We report a severe case of rhinothecal cryptococcoma in a 13-year-old female African Grey Parrot (Psittacus erithacus). The bird was born and bred in captivity in Portugal. The beak was deformed and showed several round soft masses, and microscopic examination revealed the presence of cells suggestive for Cryptococcus. Phenotypic and molecular analyses identified the obtained yeast culture as C. bacillisporus (AFLP5/VGIII). By phylogenetic analysis the parrot strain clustered with clinical C. bacillisporus strains from Mexico.